Workshop Model Pelayanan Publik Era Pemerintahan Digital - Romdana, Romdana; Peri, Peri; Gustianto , Endri; Andriani, Melatiana; Ilham, Reza Muhamad (Universitas Dehasen Bengkulu, 2022)
Governments in the digital era are increasingly adopting responsive and efficient public service models to meet the increasingly complex needs of society. Workshops have become one of the most popular approaches in developing effective public service models. This article describes a workshop model specifically designed to design, implement and evaluate innovations in public services. The main focus of the workshop is to understand community needs, design appropriate solutions, and test their implementation collaboratively. This workshop model aims to strengthen community involvement in the decision-making process and improve the quality of services provided by the government. Through a structured and participatory approach, the workshop allows stakeholders to actively contribute to crafting relevant and sustainable solutions. The article also highlights the benefits of using digital technologies in supporting the implementation of the workshop, such as online collaboration platforms and in-depth data analysis. The case studies presented in this article show that this workshop model is effective in improving the quality of public services and creating broader engagement from various stakeholders. In addition, the workshops also facilitated knowledge exchange between government agencies and communities, accelerating the adoption of best practices in public service delivery. In addition, the workshop also facilitated knowledge exchange between government agencies and the community, accelerating the adoption of best practices in public services. Overall, this workshop on public service modeling in the digital government era is a progressive step in improving transparency, accountability, and public satisfaction with services provided by the government in this digital era.